Perception of Service Quality Academic Community Faculty of Economics and Business, Universitas Negeri Surabaya - Trisnawati, Novi; Arifah, Ika Dyah Candra; Yanthi, Merlyana Dwinda; Prakoso, Albrian Fiky; Indrarini, Rachma; Kusumawati, Nunik Dwi; Robbani, Abdullah Azzam (IKIP Widya Darma Surabaya, 2025)
Objective: Service quality refers to the evaluation or overview of the extent to which a service meets or exceeds customer expectations. Continuous improvement is the most important part of achieving better performance. Of course, stakeholder expectations and desires are increasing and it is necessary to fulfill these needs so that the organization is always fit with the environment. Method: This research is included in quantitative research and uses the Servqual service quality measurement method. Respondents in this study were the Academic Community of the Faculty of Economics and Business, Unesa. Results: The results of this study, namely lecturer services, show that the level of conformity with expectations felt in the responsiveness aspect is 85.95%. Therefore, overall the total conformity between reality and expectations from the lecturer satisfaction survey is 88.85%. The results of the study on student services show that the total conformity between reality and expectations felt by students is based on the average of the mean of the five dimensions of the satisfaction survey, which is 94.63%. The results of educational staff services show that the total conformity between reality and expectations felt by educational staff from the satisfaction survey is 94.99%. This shows that overall the quality of service at FEB Unesa is very good, there are only a few items that need improvement in service improvement. Novelty: The novelty of this research lies in the simultaneous use of the SERVQUAL method to analyze service satisfaction from three main stakeholder groups (lecturers, students, and education staff) in one faculty of higher education.